2002
DOI: 10.1239/jap/1034082121
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual Galton-Watson branching process with population-size-dependent mating

Abstract: In this paper, we introduce a bisexual Galton-Watson branching process with mating function dependent on the population size in each generation. Necessary and sufficient conditions for the process to become extinct with probability 1 are investigated for two possible conditions on the sequence of mating functions. Some results for the probability generating functions associated with the process are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…In such a particular case, the model (1) may be considered under the perspective of the class of processes studied in Molina et al (2002) (1) is reduced to the class of models given in Daley (1968).…”
Section: It Is Easy To Verify That {(Zmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a particular case, the model (1) may be considered under the perspective of the class of processes studied in Molina et al (2002) (1) is reduced to the class of models given in Daley (1968).…”
Section: It Is Easy To Verify That {(Zmentioning
confidence: 99%
“…Alsmeyer and Rösler (1996), Bruss (1984), Daley (1968), González et al (2000González et al ( , 2001, Molina et al (2002) or Xing and Wang (2005). We refer the reader to Hull (2003) or Haccou et al (2005) m a n u s c r i p t 2 M. Molina et al for surveys about these processes.…”
Section: Introductionmentioning
confidence: 99%
“…By developing some techniques similar to those of Daley et al (1986) and Molina et al (2002), we obtain a criterion analogous to theirs for superadditive branching processes.…”
Section: Extinction Probability Under Condition 21mentioning
confidence: 99%
“…Molina et al (2002) suggested a bisexual Galton-Watson model with population-sizedependent mating. They obtained a necessary and sufficient condition for the process to become extinct with probability 1.…”
Section: Introduction Of Bisexual Galton-watson Branching Processesmentioning
confidence: 99%
“…In particular, the bisexual branching process with population-size dependent mating, unlike Daley's model, introduces the novelty that the function governing mating is allowed to change in each generation according to the total number of mating units in the previous generation. Some results on its extinction probability and limiting behaviour are given in Molina et al (2002) and Molina, Mota & Ramos (2004).…”
Section: Introductionmentioning
confidence: 99%